Evaluación de los forófitos de Vanilla odorata y Vanilla guianensis (Orchidaceae). en el complejo turístico Quistococha 2023 - Pizango Falcon, Joyser Miller (2024)
The study identified and evaluated the phorophytes associated with Vanilla odorata and Vanilla guianensis in the Quistococha Tourist Complex. Twelve phorophyte species were identified, including Amanoa guianensis, Ficus guianensis, Guatteria guianensis, Hevea guianensis, Himatanthus sucuuba, Lueheopsis hoehnei, Mauritia flexuosa, Mauritiella armata, Pouteria cuspidata, Tapirira guianensis, Vatairea guianensis, and Virola surinamensis. The results indicated that 73.3% of Vanilla guianensis individuals and 60% of Vanilla odorata were located in zones 4 and 5 of the phorophyte. The most frequent height of the phorophytes was between 8 and 15 metres, with diameters ranging from 12.4 to 24.9 cm for V. odorata and 15.9 to 22 cm for V. guianensis. Regarding bark characteristics, it was found that 46.7% and 40% of the phorophytes had rough bark, while 53.7% and 60% had smooth bark, inhabited by V. guianensis and V. odorata, respectively. Additionally, a significant adaptation was observed in both vanilla species, as their leaves demonstrated the ability to capture water and redirect it towards the stem, as well as to accumulate organic matter at their base. This suggests an efficient strategy for optimising nutrient absorption and the possible capacity to develop absorbent hairs at the base of the leaves in order to utilise this water collection function.